Assessing Blood Clotting and Coagulation Factors in Mice. Issue 2 (15th March 2019) - Brake, Marisa A.; Ivanciu, Lacramioara; Maroney, Susan A.; Martinez, Nicolas D.; Mast, Alan E.; Westrick, Randal J.
Abstract: The mammalian blood coagulation system was designed to restrict blood loss due to injury as well as keep the blood fluid within the blood vessels of the organism. Blood coagulation activity in inbred mouse strains varies widely among strains, suggesting that many genomic variants affect hemostasis. Some of these molecules have been discovered and characterized; however, many are still unknown. Genetically modified mouse technologies are providing a plethora of new mouse models for investigating the regulation of blood coagulation. Here we provide a protocol for the tail bleeding time as a primary assessment of in vivo blood coagulation, as well as in vitro methods such as the prothrombin time, activated partial thromboplastin time, and thrombin generation assay. We also provide protocols for the assessment of the activities of specific known factors involved in blood coagulation. © 2019 by John Wiley & Sons, Inc.